2020
DOI: 10.1007/s42452-019-1881-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction protocol on the nature and size of iron oxide nano particles obtained through solventless synthesis using iron(II)acetate: structural, magnetic and morphological studies

Abstract: Magnetite and hematite nanoparticles (~ 20 nm size) have been synthesized by solventless thermal decomposition of iron(II)acetate in air under different reaction protocols. The structure of the decomposed materials is investigated by FT-IR and powder XRD, while the morphology of the particles formed was studied by SEM/TEM. The magnetic phases of the materials are quantitatively identified by 57 Fe Mӧssbauer spectroscopy. EDX was used for elemental analysis. The results obtained from FT-IR, XRD and Mӧssbauer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…It was demonstrated that the removal of heavy metal depends also on the size of iron oxide particles [20]. The amount of heavy metal adsorption removal increased with decreasing particle size due to less aggregation and more sites exposed to adsorption [20]. We observed in TEM the smallest particles in IO-Na, less aggregation than IO-NH, IO-K samples in agreement with its high adsorption capacity.…”
Section: Heavy Metal Removalsupporting
confidence: 67%
See 1 more Smart Citation
“…It was demonstrated that the removal of heavy metal depends also on the size of iron oxide particles [20]. The amount of heavy metal adsorption removal increased with decreasing particle size due to less aggregation and more sites exposed to adsorption [20]. We observed in TEM the smallest particles in IO-Na, less aggregation than IO-NH, IO-K samples in agreement with its high adsorption capacity.…”
Section: Heavy Metal Removalsupporting
confidence: 67%
“…As shown in Figure 3, the surface area of IO-Na is high comparatively to IO-NH and IO-K samples. It was demonstrated that the removal of heavy metal depends also on the size of iron oxide particles [20]. The amount of heavy metal adsorption removal increased with decreasing particle size due to less aggregation and more sites exposed to adsorption [20].…”
Section: Heavy Metal Removalmentioning
confidence: 99%
“…The binding energy of the O 1s peak for Fe 3 O 4 is commonly at 530 eV, as illustrated in figure 5(b 2 ), and that for Fe 2 O 3 was at approximately 527 eV [34]. Moreover, the high reaction kinetics, due to the longer reaction time and higher temperature, caused an increase in the size of the nanoparticles [35]. The fast laser processing speed with controlled thermal effects realized by selecting an appropriate laser power and repetition rate can generate nanoparticles of a specific size from a liquid precursor and effectively minimise overtreatment to avoid thermal damage to both the coating and substrate.…”
Section: One-step Laser Synthesis Lidg Embedded With Fe 3 Omentioning
confidence: 96%